Pelatihan Pembuatan Sistem Pengajuan Surat Desa Dengan Sinkronisasi Data Kependudukan Desa di Website Desa - Rosanensi, Melati; Sakti, Lanang; Madani, Miftahul; Santoso, Heroe; Rahmawati, Lela (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
The Village Letter Submission System is a system, either manual or digital, used by the community to submit applications for the creation of various types of letters or official documents from the village government. This service aims to simplify the administrative process and accelerate public services at the village level, in this case the village of Akar-Akar. The village letter submission system that will be created is synchronized with the population data of the community in the village of Akar-Akar, which will later be able to access this system only the people of the village of Akar-Akar. The method used in this service is the Waterfall model or linear sequential model. This waterfall method describes a systematic and sequential approach to software development, which begins with the specification of user needs (communication) and continues through the stages of planning (planning), modeling, (modeling), construction (construction), and handover of the system/software to the user (deployment), which ends with ongoing support for the system. It is the same as the problem in the village of Akar-Akar where correspondence is still manual. Even though this village already has a website, it has not been utilized properly. A website is an information page provided via the internet, so it can be accessed anywhere as long as it is connected to the internet network. Thus, a service was carried out with the theme of training in creating a village letter submission system by synchronizing village population data on the village website. In order to facilitate correspondence in the village roots and utilize the existing website.